Boron isotope geochemistry of Na‐bicarbonate, Na‐chloride, and Ca‐chloride waters from the Northern Apennine Foredeep basin: other pieces of the sedimentary basin puzzle. Issue 4 (15th December 2014) - Boschetti, T.; Toscani, L.; Salvioli Mariani, E.
Abstract: The boron stable isotope ratio δ 11 B of 12 water samples representative of three chemical facies (fresh Na‐bicarbonate, brackish Na‐chloride, saline, and brine Ca‐chloride) has been analyzed. Interpretation of the δ 11 B data, along with the chemical compositions, reveals that Na‐carbonate waters from the Northern Apennine are of meteoric origin, with boron contributions from clay desorption and mixing with seawater‐derived fluids of Na‐chloride or Ca‐chloride compositions. The comparison of our new results with the literature data on other sedimentary basins of Mediterranean, and worldwide, confirms the contribution of Na‐bicarbonate waters to the genesis of mud volcano fluids. The Na‐chloride sample of Salvarola (SAL), which may represent the end‐member of the mud volcanoes, and the Ca‐chloride brine water from Salsomaggiore (SM) indicate boron release from clays compatible with the diagenetic process. The empirical equation: δ 11 B = [ 5.1364 × ln(1/B) mg l − 1 ] + 44.601 relating boron concentration and the stable isotope composition of the fluids observed in this study and the literature is proposed to trace the effect of diagenesis in sedimentary basins. A geothermometer associated to the diagenetic equation is also proposed: T ∘ C = [ δ 11 B − 38.873 ( ± 1.180 ) ] / [ − 0.164 ( ± 0.012 ) ] The application of this equation to obtain reservoir temperatures from δ 11 B compositions of waters should be carefully evaluated against the results obtained from other chemical and isotopic geothermometers from other basins around the world.